Recent research progress of BNCT treatment planning system - Zhaotong Wang; Qi Zheng; Bo Wang; Zhifeng Li; Jie Li; Sheng Wang; Hongbing Song; Baofeng Wang (Nuclear Engineering and Technology, 2025)
Boron neutron capture therapy (BNCT) is a type of radiation therapy that can selectively kill tumor cells. It is necessary to design a suitable treatment plan and assess its efficacy based on the actual situation of the patient before BNCT treatment. The treatment planning system (TPS) is the software used to make the treatment plans for patients, which can simulate the treatment process, adjust the parameters in the irradiation process, and calculate the dose in the patient. The TPS can select the most suitable treatment plan for patients by comparing the dose calculation results of each treatment plan, thus playing a crucial role in BNCT. This paper summarizes the main functions and requirements of BNCT treatment planning system, lists the more commonly used TPSs both domestically and internationally, introduces their main characteristics, and briefly analyzes the challenges in the development of TPS for BNCT in conjunction with the current state of BNCT treatment planning systems, so as to provide reference and guidance for the research and development of the BNCT treatment planning system.